Trends of rowing speed - Kleshnev, V. (BioRow, 2020)
The trends in rowing speeds over last 27 years (from 1993 till 2019) were recently discussed with Dr. Volker Nolte, and he voiced his concern about the decrease in speed over the last decade. As speed is significantly affected by random weather conditions, it has high variation from year to year and the trends may not be statistically reliable. In an attempt to minimise the random factor and extract trustworthy trends, the speed of the winners of the Olympics and Worlds was analysed in decades, starting from 1993-2003, 1994-2004, 1995-2005…2009-2019 with a total amount of 17 decades. In each decade, linear trends of rowing speed were determined and their slopes (the speed growth per year) were analysed.